A rebalanced transatlantic policy toward the Asia-Pacific region - Conley, Heather A.; Mina, James; Nguyễn, Phương (Center for Strategic & International Studies (CSIS) Rowman & Littlefield, 2016)
The culmination of a two-year study aiming to create a new and enduring EU-U.S. collaborative mechanism to enhance transatlantic Asia-Pacific policy coordination and understanding